Executive Committee Minutes 2013-11-14 - Academic Senate:::::::::
Agenda amended and approved. Minutes delayed. Chair Report. Provost Report. Statewide Senator Report. Vice Chair Report. Vice President of Administration and Finance Report. Follow up Discussion of the GMC hires. APC Report. ELSE Clear (Induction) Education Specialist credential program revisions approved for Senate consent calendar. Chief Student Affairs Officer Report. Associated Students Report. Senate agenda approved.